The Breastfeeding assistance improving the skill to breastfeed properly for postpartum primipara mothers - Faiqo Diyana; Tarsikah Tarsikah; Desy Dwi Cahyani (Jurnal Kesehatan Ibu dan Anak, 2020)
Breastfeeding is a natural process carried out by a mother to give nutrition for her baby directly from the breast. Some problems often occur during the process of breastfeeding, such as blisters on the nipples to mastitis. These problems cause the scope of exclusive breastfeeding not in accordance with the target set (90%). The success of breastfeeding highly depends on correct breastfeeding skills. This research aimed to determine the effect of breastfeeding assistanceon correct breastfeeding skills in primiparous postpartum mothers. This study was pre-experimental with a one-group pretest-posttest design, with a population of 30 primiparous postpartum respondents who met the inclusion criteria, using total sampling technique. The research instrument was a checklist for correct breastfeeding, the data were analyzed using the Wilcoxon Signed-Rank (a=0.05). The result of the research showed breastfeeding skill properly before assistance was unskilled (93.3%) with an average pretest value of 48.42 and after mentoring, the mothers were skilled (96.7%) with an average post-test of 82.25 with p-value 0.000. It means there is an effect of breastfeeding assistance to correct breastfeeding skills in primiparous postpartum mother. These results, it is expected that breastfeeding assistance can be used as a solution of successful program in giving breastfeeding.